Evaluation of the effect of hydrocortisone in 2D and 3D HEp-2 cell culture (Research, Society and Development, 2022)
Introduction: Cancer is one of the diseases with the highest incidence globally and that associated with the patient's emotional state, can act positively or negatively in the treatment. Cortisol is a principal primary stress hormone in the human body. The corticoids can increase cell proliferation and reactive oxygen species that contribute to DNA damage. Prolonged exposure to stress can contribute to tissues becoming insensitive to cortisol, the primary human stress hormone. Objective: This study explores cortisol's influence on tumor cell development, particularly in human cells of carcinoma of the human laryngeal (HEp-2). Methodology: HEp-2 cells were exposed to increasing cortisol (hydrocortisone) concentrations for 24 or 48 hours, and cytotoxicity (MTT assay) proliferation assay (crystal violet assay), and immunolabeled 3D culture for fibronectin and FAK were analyzed. Results: The group treated with hydrocortisone showed a significant increase in mitochondrial activity, as for the evaluation by the violet crystal, the treated group showed similar behavior to the control. The 3D culture showed dispersed cells within 24 hours with reduced FAK labeling; however, no changes were observed within 48 hours. Conclusion: Although some cases favored corticosteroid use in cancer patients, a more detailed analysis is necessary before prescribing them.